European Cloth and “Tropical” Skin: : Clothing Material and British Ideas of Health and Hygiene in Tropical Climates - Johnson, Ryan (The Johns Hopkins University Press, 2009)
As Britain’s imperial and colonial ambitions intensified toward the end of the nineteenth century, the preservation of white European health in tropical climates became an increasingly important concern. Since at least the seventeenth century, the “tropics” had been seen as spaces holding vast potential wealth but also death and disease. To combat these deadly but desirable landscapes, the British built a considerable commodity culture around the preservation of white European health, and for many, tropical clothing was one of the most important and essential items in their “kits.” This article investigates the composition and use of such clothing in relation to British ideas of health and hygiene in tropical climates. First, it considers debates that ensued over the best material—wool, cotton, linen, silk, or a combination of these materials—and the role of “black” skin and local practice in the development of tropical clothing. Second, it demonstrates the importance of location in any discussion of tropical medicine and hygiene, and the tension and ambiguity that still surrounded British ideas of health and hygiene in the tropical colonies. Third, it argues that tropical clothing was important in the maintenance of climatic etiologies despite advances in parasitology and sanitary science. Finally, it considers the relationship of tropical clothing to the formation of a unique colonial identity. To British men and women embarking for any number of tropical destinations, proper clothing was not a banal and mundane component of their outfitting. For many, the clothing signified a departure from the safe and “civil” climes of Britain for adventure in the expanding tropical empire.